2008
DOI: 10.2337/dc07-1945
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Contribution of Hostility Characteristics to High Fasting Glucose Levels

Abstract: OBJECTIVE -To assess whether psychological constructs of hostility, anger, type A behavior pattern, and depressive symptom severity 1) were associated with concurrent and prospective fasting glucose levels and 2) whether this association was moderated by marital status.RESEARCH DESIGN AND METHODS -Participants were 485 healthy men ([mean Ϯ SD] age 59 Ϯ 7 years) without a history of heart disease, diabetes, or taking related medications in the Veterans Affairs Normative Aging Study. Their fasting glucose levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 26 publications
(28 reference statements)
2
37
0
Order By: Relevance
“…Type A behavior is also thought to stimulate the HPA axis and the sympathetic nervous system [23] and an association between type A behavior and hyperglycemia was reported in a few studies [24,25]. Therefore it is possible that type A behavior is associated with the risk of diabetes; however, there are no papers that report this association as far as we know.…”
Section: Discussionmentioning
confidence: 63%
“…Type A behavior is also thought to stimulate the HPA axis and the sympathetic nervous system [23] and an association between type A behavior and hyperglycemia was reported in a few studies [24,25]. Therefore it is possible that type A behavior is associated with the risk of diabetes; however, there are no papers that report this association as far as we know.…”
Section: Discussionmentioning
confidence: 63%
“…Gonder-Frederick et al [36] reported, more than two decades ago, that hyperglycemia was associated with negative emotions (i.e., sadness, anger); a finding only recently replicated in nearly 500 healthy men [37]. Most recently, Schöpf et al [38] showed that hyperglycemia, via a glucose clamp (at 160-180 mg/L), was associated with reduced activations in limbic structures (amygdala, hippocampus, hypothalamus) to negative or positive stimuli during the hyperglycemic, compared with a euglycemic baseline, in young, healthy subjects.…”
Section: Discussionmentioning
confidence: 97%
“…One consistent consequence of perceived discrimination is the development and expression of anger and hostility (Priest et al, 2013), which have been shown to influence physiological functioning across several subsystems. For example, hostility has been associated with amplified blood pressure reactions to stress (Fredrickson et al, 2000), elevated fasting glucose (Shen, Countryman, Spiro, & Niaura, 2008), and heightened plasma lipid levels (Weidner, Sexton, McLellarn, Connor, & Matarazzo, 1987). Frequent exposure to interpersonal discrimination can be expected to occasion persistent activation of stress response systems, in particular the sympathetic nervous system and HPA.…”
Section: Discussionmentioning
confidence: 99%